2018
DOI: 10.1042/cs20171107
|View full text |Cite
|
Sign up to set email alerts
|

Altered microbiome in chronic kidney disease: systemic effects of gut-derived uremic toxins

Abstract: In chronic kidney disease (CKD), influx of urea and other retained toxins exerts a change in the gut microbiome. There is decreased number of beneficial bacteria that produce short-chain fatty acids, an essential nutrient for the colonic epithelium, concurrent with an increase in bacteria that produce uremic toxins such as indoxyl sulphate, p-cresyl sulphate, and trimethylamine-N-oxide (TMAO). Due to intestinal wall inflammation and degradation of intercellular tight junctions, gut-derived uremic toxins transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
148
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(160 citation statements)
references
References 129 publications
(170 reference statements)
3
148
1
8
Order By: Relevance
“…When homeostasis becomes unbalanced and microbial populations and functions are altered, the phenomenon is called dysbiosis. It has been directly associated [149][150][151] with the onset, progression and therapeutic response of multiple health conditions, including lung-associated disorders [152,153], obesity [154,155], diabetes [156,157], cardiovascular disease and atherosclerosis [158][159][160][161], chronic kidney disease [162][163][164], cancer [165][166][167], neurological and neuropsychiatric disorders [168][169][170][171], and, in the spirit of this review, IBD [172][173][174].…”
Section: Microbiome In Ibd: the Meta-paradigmmentioning
confidence: 96%
“…When homeostasis becomes unbalanced and microbial populations and functions are altered, the phenomenon is called dysbiosis. It has been directly associated [149][150][151] with the onset, progression and therapeutic response of multiple health conditions, including lung-associated disorders [152,153], obesity [154,155], diabetes [156,157], cardiovascular disease and atherosclerosis [158][159][160][161], chronic kidney disease [162][163][164], cancer [165][166][167], neurological and neuropsychiatric disorders [168][169][170][171], and, in the spirit of this review, IBD [172][173][174].…”
Section: Microbiome In Ibd: the Meta-paradigmmentioning
confidence: 96%
“…There is now extensive evidence that the intestinal barrier is damaged in CKD, leading to the translocation of uremic toxins originating from bacteria and other noxious luminal products into the bloodstream, resulting in inflammation, and the activation of leukocytes. Gas chromatography studies in CKD rats and end-stage kidney disease (ESKD) patients showed significant changes in exhaled breath gases compared with those of healthy controls, further evidencing the altered gut microbe composition in these patients (89).…”
Section: Gut Microbiome In Kidney Diseasementioning
confidence: 98%
“…In humans, the SCFA content in the colon region represents at least 100 mM, while its concentration ranges from 0.1 to 10 mM in the bloodstream [26]. Although decreased numbers of SCFA-producing gut microbiota in CKD or HD patients were investigated [17,18], the concentration or uptake of SCFA in this population has not extensively measured. This study also provided fundamental information about the 2-methylbutyric acid level in HD patients.…”
Section: Principal Observationsmentioning
confidence: 99%